Multisource data for seasonal variability analysis of cyanobacteria in a tropical inland aquatic environment - Cicerelli, Rejane Ennes [UNESP]; Trindade Galo, Maria de Lourdes B. [UNESP]; Roig, Henrique Llacer (Csiro Publishing, 2017)
Cyanobacterial blooms are related to eutrophic conditions that compromise the many uses of reservoirs. Thus, quick and effective methods for detecting the abundance of cyanobacteria in waterbodies are needed to complement conventional laboratory methods. In addition, inadequate control techniques that are applied at times of high cyanobacterial concentrations can cause the cells to lyse and release toxins into the water. In the present study we investigated the behaviour of cyanobacteria by determining phycocyanin and chlorophyll concentrations, using spectroradiometric and fluorometric techniques, in three field campaigns performed at the Nova Avanhandava Reservoir, Brazil. The sampling rate and favourable season for data collected had been determined previously by remote sensing analysis. Seasonal estimates of cyanobacteria were made because fluorometric sensors were able to record low concentrations, whereas the spectral analyses only detected phycocyanin at higher concentrations. Results of spectral analyses highlighted the subtle spectral characteristics indicating the presence of phycocyanin, even without a clear definition of the diagnostic features in the reflectance curve. Therefore, multiscale remote sensing complemented by fluorometric analysis and relevant environmental variables is an effective approach for monitoring cyanobacteria in Brazilian inland waters.
Keywords: fluorescence; phycocyanin; reflectance; tropical freshwater; water quality monitoring